2021
DOI: 10.31234/osf.io/ekz2u
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Free Weekly Self-Administered at-Home Virtual Reality based Protocol for Overcoming the Psychological Burden of Coronavirus: A Pragmatic Waitlist-Controlled Trial Conducted During COVID-19 lockdown in Italy with 2-week follow-up

Abstract: Background: The COVID-19 pandemic is generating extreme psychological stress associated with sadness, grief, irritability, and mood swings. Virtual reality (VR) is an immersive technology that may enhance individuals’ personal efficacy, emotional response, and wellbeing.Objective: We aimed to conduct a single-cohort, controlled trial with a 2:1 (waiting-list – VR protocol) allocation for a self-administered at-home weekly VR-based protocol for reducing the psychological burden experienced during the COVID-19 l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 68 publications
1
1
0
Order By: Relevance
“…The intervention was a weekly self-administered at-home virtual reality-based protocol consisting of two integrated parts: a 10-min 360 • VR video entitled "Secret Garden" and a series of social exercises. The obtained results indicated that the applied intervention significantly reduced the intensity of depression and stress symptoms, and the obtained results were mostly maintained in the 2-week follow-up [51]. We obtained very similar results in our research.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The intervention was a weekly self-administered at-home virtual reality-based protocol consisting of two integrated parts: a 10-min 360 • VR video entitled "Secret Garden" and a series of social exercises. The obtained results indicated that the applied intervention significantly reduced the intensity of depression and stress symptoms, and the obtained results were mostly maintained in the 2-week follow-up [51]. We obtained very similar results in our research.…”
Section: Discussionsupporting
confidence: 84%
“…Recently, the study protocol of "Secret Garden" has appeared, which adapts the ideas of a therapeutic garden to VR goggles in order to improve the mood during the COVID-19 pandemic [50]. Unfortunately, we will have to wait for the results of this study, although a preprint of an adult study has recently appeared [51]. The study was designed as a pragmatic pilot study with 40 participants.…”
Section: Discussionmentioning
confidence: 99%